The analysis and modeling of efficiency of the developed telecommunication networks on the basis of IP PBX asterisk now; 11th International Forum on Strategic Technology (IFOST 2016); Pt. 1 - Serikov T. G.; Mekhtiyev (Mekhtiev) A. Ali; Yugay V. V.; Muratova A. K.; Yakubova M. Z.; Razinkin V. P.; Okhorzina A. V.; Yurchenko A. V. Aleksey Vasilievich; Alkina A. D. (Information and communication technologies, 2016)
Title screen